Predictors of Hand Function Following Digit Replantation: Quantitative Review and Meta-Analysis. (January 2021) - Shaterian, Ashkaun; Sayadi, Lohrasb Ross; Tiourin, Ekaterina; Gardner, Daniel J.; Evans, Gregory R. D.; Leis, Amber
Background: Digit replantation affords the opportunity to restore hand function following amputation. To date, however, few studies have evaluated functional outcomes following replantation. Therefore, it was the objective of this study to perform a meta-analysis to better characterize the predictors of hand function.Methods: A literature search was performed using the PubMed database to identify studies that focused on digit amputation/replantation and functional outcomes. Studies were evaluated for patient- and injury-related factors and their respective effects on clinical outcomes of sensation, grip strength, and Disabilities of the Arm, Shoulder, and Hand (DASH) scores. Statistical analysis was conducted across the pooled data set to identify significant trends.Results: Twenty-eight studies representing 618 replanted digits were included in this study. We found the average grip strength was 78.7% (relative to contralateral), the average 2-point discrimination (2PD) was 7.8 mm, and the average DASH score was 12.81. After conducting statistical analysis, we found patients with more proximal injuries had lower grip strength scores ( P < .05). We found 2PD scores were influenced by age, mechanism of injury, and amputation level ( P < .05). Finally, we found DASH scores after replantation were predicted by mechanism of injury and level of amputation ( P < .05). The following variables did not influence outcomes: gender, tobacco use, ischemia time, and digit number.Conclusions: Digit replant does not restore premorbid hand function but does result in adequate hand function. Expected functional outcomes following replant should be considered in the decision-making process. These data can help risk-stratify patients, guide postreplant expectations, and influence the decision for replantation.